2020
DOI: 10.3390/nu12061606
|View full text |Cite
|
Sign up to set email alerts
|

Vegans, Vegetarians, and Omnivores: How Does Dietary Choice Influence Iodine Intake? A Systematic Review

Abstract: Vegan and vegetarian diets are becoming increasingly popular. Dietary restrictions may increase the risk of iodine deficiency. This systematic review aims to assess iodine intake and status in adults following a vegan or vegetarian diet in industrialised countries. A systematic review and quality assessment were conducted in the period May 2019–April 2020 according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies were identified in Ovid MEDLINE, Embase, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 60 publications
10
71
0
4
Order By: Relevance
“…The level of iodine concentration in macroalgae is not available in the Norwegian Food Composition table, except for Laver, and the iodine concentration may vary considerably within the same type of macroalgae [ 22 , 25 , 26 ]. To quantify the iodine intake from macroalgae, type of macroalgae used and self-reported amount (gram) were multiplied by mean iodine concentration in each type of macroalgae, which were based on reported iodine concentration in previous studies [ 20 , 22 , 23 , 24 ]. The types of macroalgae reported as used in this study were Sugar kelp (Saccharina latissima) , Bladder wrack ( Fucus vesiculosus ) , Wakame ( Undaria pinnatifida ), Kombu ( Laminaria japonica and Saccharina japonica ), Dulse ( Palmaria palmata ) and Laver ( Porphyra spp ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of iodine concentration in macroalgae is not available in the Norwegian Food Composition table, except for Laver, and the iodine concentration may vary considerably within the same type of macroalgae [ 22 , 25 , 26 ]. To quantify the iodine intake from macroalgae, type of macroalgae used and self-reported amount (gram) were multiplied by mean iodine concentration in each type of macroalgae, which were based on reported iodine concentration in previous studies [ 20 , 22 , 23 , 24 ]. The types of macroalgae reported as used in this study were Sugar kelp (Saccharina latissima) , Bladder wrack ( Fucus vesiculosus ) , Wakame ( Undaria pinnatifida ), Kombu ( Laminaria japonica and Saccharina japonica ), Dulse ( Palmaria palmata ) and Laver ( Porphyra spp ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, macroalgae users may be at risk of excessive iodine intake. A newly published summary regarding dietary habits in vegans and vegetarians concluded that vegans and vegetarians with no use of iodine-containing supplements or macroalgae are more susceptible to iodine deficiency and inadequate iodine intake compared to people following less restrictive diets [ 23 ]. In this study, we aimed to evaluate iodine status, dietary intake of iodine, supplement use, macroalgae use and iodine knowledge of Norwegian vegans, vegetarians and pescatarians.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a vegan diet, as more radical type, excludes all animal products. Properly balanced vegan and vegetarian diets are considered safe to follow at every stage of life, even during pregnancy and infancy [ 63 ]. However, incorrectly composed vegetarian diets can lead to a deficiency of protein, unsaturated omega-3 fatty acids, and several vitamins and minerals, such as vitamin B12, vitamin D, calcium, zinc, iron, or iodine [ 64 ].…”
Section: Diets and A Reduced Iodine Intakementioning
confidence: 99%
“…In fact, marine algae are the primary source of iodine in vegetarian diets [ 65 ]. Vegan and vegetarians who do not include marine algae in diet, or do not supplement iodine are more susceptible to iodine deficiency than individuals following a less restrictive diet [ 63 ]. Moreover, a high consumption of soy has been observed among individuals following vegetarian diets, which is the source of protein, iron, zinc or group B vitamins [ 66 ].…”
Section: Diets and A Reduced Iodine Intakementioning
confidence: 99%
“…Finalmente, una revisión sistemática que comparó la influencia de las dietas veganas, vegetarianas y omnívoras en la ingesta de yodo, encontró que tanto vegetarianos como veganos sí pueden presentar un riesgo incrementado de deficiencia de este mineral, especialmente cuando no se consumen algas o suplementos (4) . Asimismo, indica que las concentraciones de yodo en sujetos veganos se asocian, principalmente, con su ingesta dietaria, que, por diferentes razones, puede ser inadecuada.…”
Section: Estimada Editoraunclassified